Systematic Reviews and Meta-Analyses of Traditional Chinese Medicine Must Search Chinese Databases to Reduce Language Bias. (8th October 2013) - Wu, Xin-Yin; Tang, Jin-Ling; Mao, Chen; Yuan, Jin-Qiu; Qin, Ying; Chung, Vincent C. H.
Abstract : Systematic reviews (SRs) that fail to search non-English databases may miss relevant studies and cause selection bias. The bias may be particularly severe in SRs of traditional Chinese medicine (TCM) as most randomized controlled trials (RCT) in TCM are published and accessible only in Chinese. In this study we investigated how often Chinese databases were not searched in SRs of TCM, how many trials were missed, and whether a bias may occur if Chinese databases were not searched. We searched 5 databases in English and 3 in Chinese for RCTs of Chinese herbal medicine for coronary artery disease and found that 96.64% (115/119) eligible studies could be identified only from Chinese databases. In a random sample of 80 Cochrane reviews on TCM, we found that Chinese databases were only searched in 43 or 53.75%, in which almost all the included studies were identified from Chinese databases. We also compared SRs of the same topic and found that they may draw a different conclusion if Chinese databases were not searched. In conclusion, an overwhelmingly high percentage of eligible trials on TCM could only be identified in Chinese databases. Reviewers in TCM are suggested to search Chinese databases to reduce potential selection bias.